(untitled) (Bangladesh Journal of Medical Science, 2025)
Background Ophthalmic solutions, including antibiotic eye drops, antiseptic eye drops, and preservative-containing artificial tears, are commonly used in clinical practice to treat ocular infections. However, the antimicrobial efficacy of these solutions against specific ocular pathogens remains unclear. Objective This study aimed to investigate the antimicrobial properties of various ophthalmic solutions against common ocular pathogens using in vitro experiments. Specifically, we evaluated the efficacy of antibiotic eye drops (Ciprofloxacin, Tobramycin), antiseptic eye drops (Povidone-iodine), and preservativecontaining artificial tears (Benzalkonium Chloride) against clinically relevant bacteria and fungi. Methods Standardized microbial suspensions of common ocular pathogens were prepared and inoculated onto agar plates. Sterile filter paper disks impregnated with the tested ophthalmic solutions were placed on agar plates and the zones of inhibition around the disks were measured after incubation. Results Povidone-iodine exhibited superior antimicrobial activity against both Gram-positive and Gram-negative bacteria as well as against fungal pathogens. Similar trends were observed for other tested pathogens. Post-hoc analysis revealed that povidoneiodine demonstrated significantly larger zones of inhibition than the other solutions (p < 0.05). Conclusion Our study provides valuable insights into the antimicrobial properties of ophthalmic solutions against common ocular pathogens. Povidone-iodine has emerged as a promising antimicrobial agent with superior efficacy against a wide range of ocular pathogens. BJMS, Volume: 24. Supplementary Issue 2025, Page : 82-84